Heroic Epic Aesthetics in Wale Ogunyemi’s Langbodo: Towards an Ethical Approach (SCHOLARS: Journal of Arts & Humanities, 2025)
The epic tradition in literary history has always celebrated the great actions of one or more legendary heroes from a community who performed extraordinary and superhuman exploits in the interest of their community. Such heroes often engaged in highly challenging and perilous voyages, life-and-death battles, and other extraordinary exploits to protect or promote their human societies. A close study of Wale Ogunyemi’s Langbodo provides us with a paradigm for heroic epic in African drama. Hence, using a ‘genresical approach,’ this paper examines the aesthetics of heroic epic in African drama with a particular focus on Ogunyemi’s work. It avouches that the play is concerned with human heroic exploits and superhuman deeds which place the protagonist among epic characters, and that genuine heroism lies on duty, courage, persistency, and discipline, among others. Precisely, the lead character , Ogunyemi’s play exposes human foibles and, as a typical heroic epic, beyond conveying the heroic attributes of the lead character in the epic.